Prevalence and Factors Associated with BRCA1/2 Gene Mutation in Chinese Populations with Breast Cancer - Huang G; Lu H; Chen Q; Huang X (International Journal of General Medicine, 2022)
Guoding Huang, Hongquan Lu, Qizhu Chen, Xinting Huang Department of Oncology, The Central Hospital of Western Area of Hainan, Danzhou, Hainan, People’s Republic of ChinaCorrespondence: Guoding Huang, Department of Oncology, The Central Hospital of Western Area of Hainan, Danzhou, Hainan, People’s Republic of China, Tel +86-898-23836851, Fax +86-898-23836853, Email huangguoding123@gmail.comObjective: We aimed to evaluate the prevalence of BRCA1 and BRCA2 mutations in Chinese populations with breast cancer. Factors associated with BRCA1 and BRCA2 mutations are also evaluated.Methods: This was a cross-sectional study, and patients with breast cancer were included. Data on clinical characteristics, information of breast cancer, and BRCA1 and BRCA2 mutations were extracted. Patients were divided into the carrier and noncarrier groups.Results: A total of 368 patients were included. Compared to the noncarrier group (n = 240), patients in the carrier group (n = 128) were younger and more likely to have breast cancer at age < 40 years. Of the overall 128 patients in the carrier groups, 58 had BRCA1 mutation and 70 had BRCA2 mutation. Among patients with early onset breast cancer, there was no difference in the prevalence of BRCA1 and BRCA2 (20.7% vs 17.1%, P = 0.35). While among patients with a family history of breast/ovarian cancer, BRCA2 mutation was more prevalent than BRCA1 mutation (54.3% vs 44.8%, P = 0.01); and among patients with triple-negative breast cancer, BRCA1 mutation was more prevalent than BRCA2 mutation (34.5% vs 28.6%, P = 0.04). After adjusting for covariates, factors associated with BRCA1 mutation included breast cancer diagnosed < 40 years, tumor size > 2 cm, and lymph node metastasis; and after adjusting for covariates, factors associated with BRCA2 mutation included age, tumor size > 2 cm, and triple-negative breast cancer.Conclusion: The prevalence of BRCA1 and BRCA2 mutations varied according to three specific subgroups. Factors associated with BRCA1 and BRCA2 mutations were differential.Keywords: breast cancer, prevalence, predictors, breast cancer-associated gene